Impact of Digital Mentorship on WomeninSTEM - Aguilar Montoya, Douglas Adalberto; Martinez Almendares, Wendy Stephanie (LACCEI, 2025)
Female student dropout in STEM disciplines constitutes a structural problem in Latin America, with rates of 45% during the first two years of engineering. This study analyzes the impact of virtual mentoring programs on the academic retention of women in STEM careers (2020–2024). Through a longitudinal analysis of 1,247 students across 15 universities in 8 Latin American countries, three models of virtual mentoring were evaluated: peer-to-peer, professional-to-student, and group mentoring. The results show that participants in digital mentoring demonstrated 23% higher academic retention (78.4% vs. 55.1%) compared to the control group. In El Salvador, where women represent only 17% of graduates in engineering and technology, students engaged in digital mentoring recorded a 31% increase in academic retention. The hybrid peer-to-peer model combined with professional mentoring proved most effective in the early years. Virtual mentoring represents a scalable and cost-effective strategy to reduce the gender gap in STEM.